Pengaruh Silase Rumput Kume dan Alysicarpus Vaginalis dengan Imbangan yang Berbeda terhadap Kecernaan Bahan Kering, Bahan Organik dan Metabolisme Energi Secara In Vitro - Say, Yohanes K.; Nikolaus, Tara T.; Lestari, Gusti A. Y. (Yayasan Sumber Daya Manusia Cerdas, 2024)
This research was carried out with the aim of knowing the effect of silage of Kumegrass and Alysicarpus vaginalis (L.) with different balances on the energy value of silage in vitro and to determine the best balance of silage energy. . This research was conducted at the UPTD Integrated Field Laboratory of Archipelago Dry Land, University of Nusa Cendana, Kupang. This study was conducted for 60 days. The method used is a fully randomized design (CRD) experimental method with 4 treatments and 16 replicates. The treatments tried were; AV₀: kumegrass 100% + scalp hair 5%, AV₂₀: kumegrass 80% + Alysicarpus vaginalis 20% + scalp hair 5%, AV₄₀: kumegrass 60% + Alysicarpus vaginalis 40% + scalp hair 5%, AV₆₀: kumegrass 40% + Alysicarpus vaginalis 60% + Pollard 5% . The parameters measured digestibility of dry matter(IVDMD), digestibility of organic matter (IVOMD), and energy metabolism (EM). These data were obtained by analysis of variance (ANOVA) using spss 21 digestibility of dry matter and organic matter. It was concluded that the use of AV₆₀ levels in kumegrass silage and Alysicarpus vaginalis could increase digestibility of dry matter, digestibility of organic matter and energy levels.